Options for the development of coagulopathy in COVID-19 (Eurasian Medical Research Periodical, 2023)
The mechanisms of COVID-19-associated coagulopathy (CAC) are complex and differ in many ways from the standard mechanisms of thrombosis in critically ill patients. This review presents the pathogenesis, diagnosis and comparison of different types of coagulopathy with SAS. In the course of COVID-19 infection, the number of cases of sudden death outside the hospital has increased. One possible reason is the high rate of serious thrombotic events in patients with COVID-19. However, the pathogenesis of these life-threatening events is multifactorial and requires independent discussion